For test point x = –2, the inequality is true.
For test point x = 0, the inequality is false.
For test point
, the inequality is true.
For test point x = 2, the inequality is false.
Solution:
Given expression is the inequality.
![$(5 x-3)/((x-1)(x+1)) \leq 0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/3oyf42kjx48tgroqllno4tojeqxfpzbxo8.png)
Substitute x = –2 in the inequality.
![$(5 (-2)-3)/((-2-1)(-2+1) )=(-13)/((-3)(-1) )](https://img.qammunity.org/2021/formulas/mathematics/middle-school/p14649srt6u7k4xwah0qmip39ujifqfajj.png)
![$=(-13)/(3 )](https://img.qammunity.org/2021/formulas/mathematics/middle-school/crbhik9opwazanvq78ma4imybd2jjb6whf.png)
< 0
For test point x = –2, the inequality is true.
Substitute x = 0 in the inequality.
![$(5 (0)-3)/((0-1)(0+1) )=(-3)/((-1)(1) )](https://img.qammunity.org/2021/formulas/mathematics/middle-school/o8gyc72g9lo6uzljcch7gxxnctc19wztgt.png)
![$=3](https://img.qammunity.org/2021/formulas/mathematics/middle-school/m7is7yy754ll693jg2kap4t35jey5qj0kg.png)
> 0
For test point x = 0, the inequality is false.
Substitute
in the inequality.
![$(5 ((4)/(5) )-3)/((((4)/(5) )-1)(((4)/(5) )+1) )=(1)/((-(1)/(5) )((9)/(5) ) )](https://img.qammunity.org/2021/formulas/mathematics/middle-school/1k3bv7s5bbas2u3bbfxijm92l4rzxah548.png)
![$=(-25)/(9 )](https://img.qammunity.org/2021/formulas/mathematics/middle-school/lepmskbex0k7ebcyftagxvnu0pdobdnq0k.png)
< 0
For test point
, the inequality is true.
Substitute x = 2 in the inequality.
![$(5 (2)-3)/((2-1)(2+1) )=(7)/((1)(3) )](https://img.qammunity.org/2021/formulas/mathematics/middle-school/lwtwvtcjdvr3ha58zsedlv67q9okges4pw.png)
![$=(7)/(3 )](https://img.qammunity.org/2021/formulas/mathematics/middle-school/otjgzbnca55nsp3bra1vyfwh4grr6s269g.png)
> 0
For test point x = 2, the inequality is false.
Hence,
For test point x = –2, the inequality is true.
For test point x = 0, the inequality is false.
For test point
, the inequality is true.
For test point x = 2, the inequality is false.